THE ROLE OF PARENTAL ATTENTION AND LEARNING MOTIVATION IN INCREASING STUDENTS’ ENGLISH LEARNING ACHIEVEMENT - Viviana Lisma Lestari (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2020)
The purpose of this study was to determine the effect of parents' attention on learning achievement in English, the effect of learning motivation on learning achievement in English and to determine the effect of parents' attention and motivation to learn on learning achievement in English simultaneously. The research method used was a survey. The sample size was 52 students; with the sampling technique used was random sampling. Hypothesis testing uses 2-way ANOVA test. The results showed that there was a significant influence of parents' attention and motivation to learn together on students' English learning achievement at MTsN 6 East Jakarta, as evidenced by the value of Sig = 0,000 < 0.05 and F count = 26.255. There was a significant influence of parents’ attention on students' English learning achievement at MTsN 6 East Jakarta, as evidenced by the value of Sig = 0.001 < 0.05 and t arithmetic = 3.380. There was a significant influence of learning motivation on students' English learning achievement in MTsN 6 East Jakarta, as evidenced by the value of Sig = 0.004 < 0.05. Parental attention and learning motivation had a significant effect on learning achievement.